Crystal structure of (Z)-2-(1-benzyl-2oxoindolin-3-ylidene)-N-phenylhydrazine-1-carbothioamide. (March 2015) - Vimala, G.; Haribabu, J.; Karvembu, R.; Kumar, B. V. N. Phani; SubbiahPandi, A.
No abstract available